Seamus Heaney, 1939-2013 - Harmon, Maurice (ABEI Journal, 2013)
Seamus Heaney explores the historical and cultural origins of his native territory. His poems link to its landscape in loving recreations of activitiesand customs and in troubled assessment of sectarian divisions. Poetry becomes a means of redressing wrongs, of balancing opposing tensions. The question of the poet’s responsibility and of the value of poetry itself becomes central. Ultimately he must be true to himself, have freedom to express himself, and live in the republic of his own conscience.Keywords: Seamus Heaney; contemporary Irish poetry; poet’s responsibility.